Factors Affecting of Academic Administration of School under the Rayong Primary Educational Service Area Office 1 - เทพไพฑูรย์, โสฬส; รักษ์นคร, กุลจิรา; คงเที่ยง, สมศักดิ์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
The objectives of this research were: 1) to examine the level of factors affecting academic administration in schools 2) to study the state of academic administration in schools 3) to investigate the relationship between factors affecting academic administration in schools and 4) Factors affecting academic administration in schools under the Rayong Primary Educational Service Area Office 1. The sample group consisted of 339 teachers under the Rayong Primary Educational Service Area Office 1, determined according to Yamane's table (Yamane, 1967) by simple random sampling. The research instrument was a 5-level Likert scale questionnaire with a content validity index between .80 to 1, with a reliability coefficient of .97. Data were analyzed using percentage, mean, standard deviation, Pearson Product Moment Correlation, and Stepwise Multiple Regression Analysis.           The results were 1) The factors affecting academic administration in schools were overall at a high level. When considered in individual aspects, they are at the high to the highest level. 2) The state of academic administration in schools was overall at the highest level. When considered in individual aspects, they are at the high to the highest level. 3) The relationship between the factors affecting academic administration in schools was at a high level (r= .798) with statistical significance at the .01 level. 4) The factors affecting academic administration consisted of Media and Educational Technology (x6), Budget (x4), Parents and Community (x3), Administrator’s Leadership (x1) and Teachers (x2). These factors had a linear relationship with academic administration with statistical significance at the .01 level and could predict the academic administration with an efficiency of 63.98 percent. The predictive equations were as follows. Predictive Equation in Raw Scores:   Y = .988+.184x6+.133x4+.160x3+.158x1+.152x2 Predictive Equation in Standardized Scores:  ZY = .226x6+.184x4+.230x3+.189x1+.163x2